APEC summit: Thailand's middle power diplomacy - Pitakdumrongkit, Kaewkamol (2023)
It was in this challenging environment that Thailand hosted the 29th APEC Economic Leaders Meeting in Bangkok, 17-19 November 2022. Critics had doubted whether a Leaders’ Declaration would be possible. Against all odds, the outcomes of APEC 2022 were better than expected.